INFLUENCE OF BRANDING ON THE INDIAN CONSUMER’S PURCHASE DECISIONS FOR MOBILE PHONES - Garg, Nitasha (2012)
Mobile phones are the most frequently used device used by the individuals on daily basis. This, demand for mobile phones have brought about a high level of competition amongst the suppliers. More and more companies are entering this market. With this huge demand and supply the concept of consumer empowerment has come into place. With the introduction of a huge chunk of players in the market the consumers seek to find the right deal for them amongst the huge choices available.